2010
DOI: 10.1142/s0217979210064393
|View full text |Cite
|
Sign up to set email alerts
|

ELECTRICAL AND MAGNETIC BEHAVIOR OF TRANSITION METAL OXIDES Ln0.7A0.3TMO3, Ln= La, Pr; A = Ca, Sr AND TM = Mn, Co

Abstract: We present a detailed magnetic study of the polycrystalline transition metal oxides Ln 0.7 A 0.3 TMO 3, Ln = La , Pr ; A = Ca , Sr and TM = Mn , Co at low temperatures including electrical resistance, magnetization and ac susceptibility measurements. The effect of the A-site and B-site substitutions on the properties of these compounds is discussed. The results of this analysis indicate that the electrical and magnetic behavior of these compounds have some reminiscences of the manganites having similar formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The shape of the M (T ) curve for this sample was rather complex, not typical for pure ferromagnets, with a maximum in M ZF C (T) at T f ∼ 16 K and a frequency dependent maximum in ac susceptibility (not shown), both in the real part χ (T ) and in the imaginary part χ (T ) [6,8]. The ferromagnetic transition temperatures increase with increasing Sr content in the samples.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The shape of the M (T ) curve for this sample was rather complex, not typical for pure ferromagnets, with a maximum in M ZF C (T) at T f ∼ 16 K and a frequency dependent maximum in ac susceptibility (not shown), both in the real part χ (T ) and in the imaginary part χ (T ) [6,8]. The ferromagnetic transition temperatures increase with increasing Sr content in the samples.…”
Section: Resultsmentioning
confidence: 84%
“…The bifurcation between M ZF C (T ) and M F C (T ) curves is typical for doped cobaltites [3][4][5][6][7][8][9][10][11][12][13][14][15]16]. No saturation was seen in M (H) curves for any of the samples, even up to 12 T. Such a behavior suggests the coexistence of a dominant ferromagnetic phase together with a non-ferromagnetic one, i.e., a phase separation scenario.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…While studies by I.G. Diack et al [ 28 ] in the and systems have shown that T C decreases with increasing cobalt content. In order to widen the field of investigation, especially the search for materials with possibility to be used in magnetic or electrical devices, we studied the properties of some manganites derived from the compound Pr 0.7 Sr 0.3 MnO 3 [ 29 ], whose lanthanide (or rare earth) is praseodymium, much less studied than its counterpart lanthanum.…”
Section: Introductionmentioning
confidence: 97%